Model Kebijakan Dividen pada Bank Pembangunan Daerah di Indonesia dengan Ukuran Perusahaan Sebagai Moderasi - Sindy Friska Alfiana; Linda Purnama Sari (Universitas Hayam Wuruk Perbanas, 2025)
Dividend policy is an important corporate decision in determining the proportion of profits distributed to shareholders and reflects a company’s financial condition and performance. This study aims to analyze the effect of profitability, liquidity, and capital adequacy on dividend policy, with firm size as a moderating variable, in Regional Development Banks (BPD) in Indonesia during the 2020–2024 period. The research problem focuses on differences in dividend policies among BPDs and the financial factors influencing them. This study uses secondary data in the form of annual financial statements obtained from the official website of the Financial Services Authority (OJK). The sampling method employed was purposive sampling, resulting in a sample of 24 BPDs with a total of 120 observations. Data analysis techniques include descriptive statistical analysis, multiple linear regression, and Moderated Regression Analysis (MRA). The results indicate that profitability has a positive and significant effect on dividend policy, liquidity has a positive but insignificant effect, and capital adequacy has a negative and significant effect on dividend policy. Firm size is unable to moderate the effect of profitability and liquidity on dividend policy. The findings may serve as a consideration for BPD management in making dividend distribution decisions.